2020
DOI: 10.1007/978-981-15-5414-8_16
|View full text |Cite
|
Sign up to set email alerts
|

Lie Symmetry Analysis to General Fifth-Order Time-Fractional Korteweg-de-Vries Equation and Its Explicit Solution

Abstract: In this research paper, we have discussed a systematic approach to solve the general time fractional fifth-order Korteweg-de-Vries equation (KdV) by Lie Symmetry Analysis. Similarity reduction transformed the fractional-order partial differential equation (FPDE) into a nonlinear fractional ordinary differential equation with new independent variable. Erdelyi-Kober fractional differential and integral operator depend on parameter 'α' implemented to reduce into fractional ordinary differential equation (FODE). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Now for further solution of FODEs, we want to explore the explicit power series solution [30,31], which can be applied to solve FODE (37).…”
Section: Power Series Solution Of Bmmentioning
confidence: 99%
See 2 more Smart Citations
“…Now for further solution of FODEs, we want to explore the explicit power series solution [30,31], which can be applied to solve FODE (37).…”
Section: Power Series Solution Of Bmmentioning
confidence: 99%
“…Jafari et al [16] explored the numerical scheme to study the system of fractional PDEs. Gandhi et al [30][31][32][33][34] provided the explicit solution of fifth-order and fourth-order fractional systems by Lie symmetry analysis. He has been discussed about brain cancer tumor growth model and its analytic solution by the application of fractional reduced differential transform method on Burgess equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chauhan and Arora [29] has obtained the complete analysis of time fractional Kupershmidt equation. Recently, Gandhi et al [40,41,50] have applied symmetry reduction on multi-ordered time-fractional KdV equations and Hirota-Satsoma-coupled Korteveg-de-Vries equations to obtain the explicit solutions with convergence and conservation laws; he concluded that the fractional-order parameter  can control the output of solution of fractional mathematical models and in physical and mathematical aspects, the conservation laws play very crucial role to discuss the consistency of system. Zhang et al [45] promoted the 3 conservation laws of Fokkar-Plank equation with power diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Chauhan and Arora [41] obtained the complete analysis of the time fractional Kupershmidt equation. Recently, Gandhi et al [42][43][44] applied symmetry reduction on multiordered time-fractional KdV equations and Hirota-Satsoma-coupled Korteveg-de Vries equations to obtain the explicit solutions with convergence and conservation laws. Zhang et al [45] exploited the conservation laws of the Fokkar-Plank equation with power diffusion.…”
Section: Introductionmentioning
confidence: 99%